THE EFFECT OF SOCIAL MEDIA ON UNDERSTANDING OF ISLAMIC RELIGIOUS EDUCATION IN GEN Z: Case Study: As Syafi'iyah Islamic University, Bekasi City - Moch Zadit Taqwa Al Isro’i; Muhajir Purwodirekso; Muallimah Rodhiyana (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Islamic religious education must be comprehensively understood to become a guide in social and community life. In the era of advances in technology and information, individual understanding of Islamic religious education is more or less influenced by advances in technology and information. This study aims to determine whether social media influences the understanding of Islamic Religious Education gen Z during the Covid-19 pandemic in As-Syafi'iyah Islamic University students, Bekasi city. The method used in this study is a quantitative method with a sampling technique using simple random sampling with a sample of 96 people and data collection techniques using a questionnaire with a Likert scale 4. Furthermore, the data is analyzed by statistical calculations, simple regression analysis, and correlational tests using the SPSS program. 24 for Windows. The results showed that the correlational test (t count = 4,177 > t table = 1,985). Because of the count > t table, H0 is rejected, and H1 is accepted. Social media affects understanding gen z Islamic religious education during the COVID-19 pandemic for students at the As Syafi'iyah Islamic University in Bekasi. These results show that social media is one of the important factors in supporting and providing an understanding of Islamic Religious Education for gen z during the covid-19 pandemic. Rendahnya pemahaman Pendidikan islam secara garis besar disebabkan oleh faktor dari dalam diri dan faktor lingkungan. Pemahaman Pendidikan agama islam merupakan modal utama dalam menjalani kehidupan beragama dan bermasyarakat. Pemahaman Pendidikan agama islam yang kuat dan mapan dapat dijadikan pedoman dalam berkehidupan sosial dan masyarakat. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh antara media sosial terhadap pemahaman Pendidikan Agama Islam gen Z di masa pandemi Covid-19 pada mahasiswa Universitas Islam As-Syafi'iyah kota Bekasi. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan teknik pengambilan sampel menggunakan simple random sampling dengan jumlah sampel 96 orang dan Teknik pengumpulan data menggunakan kuesioner dengan skala likert 4. Selanjutnya data di analisis dengan perhitungan statistic analisis regresi sederhana dan uji korelasional menggunakan bantuan program SPSS 24 for Windows. Hasil penelitian menunjukkan bahwa pada uji korelasional (thitung = 4,177 > ttabel =1,985). Karena thitung > ttabel maka H0 ditolak dan H1 diterima. Artinya media sosial berpengaruh terhadap pemahaman Pendidikan agama islam gen z di masa pandemic covid-19 pada mahasiswa Universitas Islam As Syafi’iyah kota Bekasi. Dari hasil tersebut menunjukkan bahwa media sosial menjadi salah satu faktor penting dalam menunjang dan memberikan pemahaman Pendidikan Agama Islam kaum gen z di masa pandemic covid-19.